Ketidakseimbangan Pembuktian dalam Perselisihan Hasil Pemilu di Mahkamah Konstitusi: Antara Hukum dan Kepentingan Politik - Sultan Reza Islami; Sidi Ahyar Wiraguna (Lembaga Pengembangan Kinerja Dosen, 2025)
Disputes over general election results (PHPU) at the Constitutional Court reflect the critical role of evidence in resolving electoral conflicts. However, in practice, there exists an imbalance in the evidentiary process between the disputing parties. This study aims to analyze such disparities using a normative juridical approach by examining laws and regulations, Constitutional Court decisions, and relevant legal literature. The findings indicate that evidentiary issues in PHPU are influenced not only by formal and material legal aspects but also by the political dynamics that accompany every electoral contest. Unequal access to evidence, disparities in evidentiary capacity among parties, and the Court’s limited ability to conduct active examinations exacerbate this imbalance. Additionally, political interests often influence perceptions of the independence of evidence and the objectivity of court decisions. Therefore, there is a pressing need to strengthen technical regulations on evidence, enhance the evidentiary capacity of disputing parties, and optimize the Constitutional Court’s role in maintaining balance in the evidentiary process. In conclusion, the imbalance of evidence in PHPU at the Constitutional Court stems not only from procedural weaknesses but also from the political interests surrounding the trial process. Reforming the evidentiary system is urgently needed to uphold the principles of electoral justice in Indonesia.